2004
DOI: 10.1038/sj.jhh.1001671
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic and parasympathetic activation in heart rate variability in male hypertensive patients under mental stress

Abstract: Disturbed sympathetic and also parasympathetic activity of the autonomic nervous system points to pathological alterations in the cardiovascular system. Untreated hypertensive subjects were examined with respect to the question of whether an increase in sympathetic activity necessarily goes along with a reduction in parasympathetic activity, and whether 'delayed' recovery behaviour after mental stress could be an indicator of a disturbed cardiovascular function. In 20 male hypertensive (HT) and 20 normotensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 25 publications
4
47
0
1
Order By: Relevance
“…These results coincide with previous findings (Hjortskov et al, 2004;Ruediger et al, 2004;Lampert, et al, 2005;Lane et al, 1992). It is believed that HF reflects the vagal control of S-A node, one important aspect of the parasympathetic control of ANS of the heart .…”
Section: Hf Changes From Rest To Stresssupporting
confidence: 83%
See 2 more Smart Citations
“…These results coincide with previous findings (Hjortskov et al, 2004;Ruediger et al, 2004;Lampert, et al, 2005;Lane et al, 1992). It is believed that HF reflects the vagal control of S-A node, one important aspect of the parasympathetic control of ANS of the heart .…”
Section: Hf Changes From Rest To Stresssupporting
confidence: 83%
“…Specifically, studies examining HRV parameters during mental stress demonstrated the autonomic imbalance of the heart regulation, which was not evident at rest alone (Gianaros et al, 2005;Ruediger, Seibt, Scheuch, Krause, & Alam, 2004).…”
Section: Mental Stress and Hrvmentioning
confidence: 99%
See 1 more Smart Citation
“…Haemodynamic parameters are controlled, to some extent, by the autonomic nervous system. The activity of the autonomic nervous system is reflected in the heart rate variability (HRV) [6][7][8]. Several authors have demonstrated depressed long-term HRV in patients with underlying cardiovascular disease [9][10][11] and HRV has proved to be highly predictive for cardiovascular morbidity and mortality in these patients [12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown in a number of studies that during mental stress, there is an increase in sympathetic activity and a decrease in parasympathetic activity [7,8]. This results in increased strain on the heart, immune and hormonal systems.…”
Section: Introductionmentioning
confidence: 99%